Drop jump? Single-leg squat? Not if you aim to predict anterior cruciate ligament injury from real-time clinical assessment: A prospective cohort study involving 880 elite female athletes - Petushek, E.; Nilstad, A.; Bahr, R.; Krosshaug, T. (Journal of Orthopaedic & Sports Physical Therapy, 2021)
Objective: To determine whether visually assessed performances of the single-leg squat (SLS) and vertical drop jump (VDJ) were associated with future noncontact anterior cruciate ligament (ACL) injury. Design: Prognostic accuracy cohort study. Methods: Elite female handball and football (soccer) athletes (n = 880) were tested from 2007 to 2014 and tracked through 2015. Trained physical therapists visually rated each leg during a SLS and overall control during a VDJ. Receiver operating characteristic curve, Pearson chi-square, and logistic regression analyses were used to determine the prognostic accuracy of the 2 screening tests. Results: Sixty-five noncontact ACL injuries occurred during the follow-up period. Fourteen percent of athletes who sustained an ACL injury had poor SLS performance, compared to 17% of the noninjured athletes (P = .52 and .67 for hip and knee ratings, respectively). Side-to-side asymmetry in the SLS was not different between injured and noninjured athletes (P = .10 and .99 for hip and knee asymmetry, respectively). Twenty-one percent of athletes who sustained an ACL injury had a poor VDJ rating, compared to 27% of the noninjured athletes (P = .09). Furthermore, area under the curve values ranged from 0.43 to 0.54 for the SLS and VDJ, demonstrating no to poor prognostic accuracy. Conclusion: Neither SLS nor VDJ test performance distinguished between athletes who sustained a subsequent noncontact ACL injury and those who did not.